Ucrania, un Estado y dos civilizaciones - Granados, Javier (UNISCI Discussion Papers, 2007)
This article deals with the roots of the current division between civilizations in Ukraine (Western and Slavic-Orthodox) and its consequences for that country’s domestic and foreign policies. The author claims that this division started to form in the 12th century, while the Kievan Rus State was missing, and it has reached the dawns of the 21st century. He points out that the existence in Ukraine of an Orthodox civilization does not mean that those belonging to it are in favour of a political union with Russia. They are Ukrainians who share many aspects of the Russian culture and, at the same time, defend the sovereignity of their country against a possible union with Russia. The author concludes that this difference between civilizations existing today in Ukraine tends to weaken, tough not to disappear.